Endothelial Dysfunction and Cardiovascular Disease: History and Analysis of the Clinical Utility of the Relationship - Peter J. Little; Christopher D. Askew; Suowen Xu; Danielle Kamato (Biomedicines, 2021)
The endothelium is the single-cell monolayer that lines the entire vasculature. The endothelium has a barrier function to separate blood from organs and tissues but also has an increasingly appreciated role in anti-coagulation, vascular senescence, endocrine secretion, suppression of inflammation and beyond. In modern times, endothelial cells have been identified as the source of major endocrine and vaso-regulatory factors principally the dissolved lipophilic vosodilating gas, nitric oxide and the potent vascular constricting G protein receptor agonists, the peptide endothelin. The role of the endothelium can be conveniently conceptualized. Continued investigations of the mechanism of endothelial dysfunction will lead to novel therapies for cardiovascular disease. In this review, we discuss the impact of endothelial dysfunction on cardiovascular disease and assess the clinical relevance of endothelial dysfunction.